Advantage of pegylated interferon and ribavirin combination therapy in people living with hepatitis C virus/HIV coinfection. Issue 1 (January 2016) - Qadir, Muhammad Imran; Arooj, Javaria
Abstract : Nearly one-third of people with HIV are also infected with hepatitis C virus (HCV). HIV/HCV coinfection is coupled with a more rapid rate of hepatitis C disease development, elevated HCV viral load, and a greater possibility of severe liver damage. Treatment should be initially started with antiviral drugs so that virus can be eradicated and chances of development of cirrhosis can be reduced. HIV and HCV should not be cotreated at the same time as it will result in outburst of side-effects in which the responsible drug cannot be identified. Mainly people living with HCV/AIDS should be treated with pegylated interferon along with ribavirin combination therapy. Pegylated interferon is more helpful because it has longer serum decay time than the interferon alone, and therefore assists in single weekly dosing. Majority of studies show that small dose of ribavirin, that is, 800 mg daily, is more advantageous in HIV/HCV coinfection, rather than higher doses that are effective in HCV monotherapy.